Investigate on surface/subsurface damage mechanisms and manufacturability of ultra-smooth surface in ultra-precision ductile grinding of sapphire optics - Sheng Wang; Qinghe Zhang; Qingliang Zhao; Ming Zhou (Journal of Materials Research and Technology)
Sapphire is a kind of high hard-brittle transparent single crystal material with excellent comprehensive properties in the aspects of mechanics, thermology and optics, which can be widely used in aviation, aerospace, medical treatment, high-energy laser and consumer electronics etc., especially in the service environments of high-temperature, high-pressure, and high-speed of the infrared field. Sapphire is the most ideal material for manufacturing complex curved optics of the advanced air vehicle. However, due to the extremely high hardness and fracture toughness of sapphire that has brought unprecedented huge challenges for the ultra-precision grinding techniques in terms of surface/subsurface damage characteristics and evolution mechanisms. In this paper, the surface/subsurface damage mechanisms and manufacturability of ultra-smooth surface in ultra-precision ductile grinding of sapphire were systematically investigated. Firstly, the manufacturing methods of the traditional ultra-smooth surface and their advantages and disadvantages were systematically investigated and discussed, and the formation principle in ultra-precision grinding of large-size sapphire complex surface optics with ultra-smooth surface was proposed. Secondly, the evolution characteristics of surface roughness, surface morphology and surface damage with the reduction of grain size of grinding wheel were studied. Thirdly, the subsurface damage mechanisms and microscopic characteristics in ultra-precision grinding of sapphire were researched, and the evolution processes and removal mechanisms of surface/subsurface damage were revealed. Then, the subsurface damage characteristics and evolution mechanisms in ultra-precision ductile grinding of sapphire were thoroughly researched based on TEM images. Ultimately, a sapphire planar optics with sub-nanoscale surface roughness, smooth ductile grinding surface and ductile subsurface were achieved.